Remote Legal Research Training for the 'Denmark–Myanmar Programme on Rule of Law and Human Rights' During the Pandemic. (September 2020) - Bird, Ruth
Abstract: The impact of the Covid 19 lockdown of Western countries has had extensive coverage, but for other countries, like Myanmar, little information has been shared in the Western media. Yet the impact on everyday activities there has been just as great, including closure of workplaces and universities, the wearing of masks, and restrictions on travellers from outside Myanmar. When a planned programme of face-to-face legal research teaching in May 2020 could not be offered, another means had to be found to deliver a course which had been successfully introduced the previous year. In this article Ruth Bird outlines how the course went ahead even though she was in lockdown in Melbourne, while her colleagues and participants were locked down in Yangon.